Charting the course through a perilous future : are NBS graduates and courses ready? - Choo, Huey Shan. (2008)
This study seeks to explore the differences in requirements of auditors from a public accounting perspective (Big Five and Non Big five firms) as well as the government perspective (Auditor General’s Office). The training programmes provided by various organizations are also examined, to find out the areas of interest to the employers.